Kananaskis country’s road to coexistence: exploring expert perceptions of roadside bear viewing and management strategies - Pumphrey, Annie; Meletis, Zoë A. (Frontiers in Conservation Science, 2023)
In North America, bear viewing is becoming increasingly popular with visitors to parks and protected areas. In the face of heightened visitation pressures in parks, the phenomena of roadside bear viewing poses risks to humans and wildlife. A related challenge is the formation of “bear jams,” which is traffic congestion caused by people stopping or slowing down to view bears. Using Peter Lougheed Provincial Park (PLPP) in Kananaskis, Alberta, as a case study, we examined the gaps in our understanding of roadside bear viewing from a human dimensions approach. To gain insight into management strategies, risks, and observed human behavior associated with roadside bear viewing, semi-structured interviews (n=22) were conducted with expert participants, including park staff members, non-profit organization employees, and biologists. Responses emphasized the need for consistent messaging and better communication regarding respectful roadside bear viewing behaviors, and recommendations for specific forms and methods of communication. Results of this study indicate that a holistic and adaptive approach could mitigate roadside bear viewing risks while also balancing conservation and recreation goals. Among the key contributions of this study is its insight into roadside bear management and viewing from a social sciences and human dimensions perspective